Preference for Prompting Procedures to Address Escape-Maintained Behavior in Autistic Adolescents. - Scheithauer, Mindy C.; Bottini, Summer B.; McMahon, Meara X. H. (Journal of Developmental & Physical Disabilities, 2025)
Differential reinforcement of alternative behavior (DRA) is a common strategy for escape-maintained behaviors targeted for reduction (i.e., targeted behavior) exhibited by youth with intellectual and developmental disabilities. DRA often involves various methods of prompting to ensure the instruction or task remains in place until contingencies for the DRA are met. Currently, there is little research on client preference for these different prompting strategies in the context of DRA treatments. The current study includes four participants diagnosed with autism spectrum disorder (ASD) who exhibited targeted behavior maintained by escape from instructional tasks. We evaluated efficacy and preference for three prompting strategies (three-step least-to-most, repeated vocal prompt, or a single initial prompt) embedded in a DRA treatment aimed at reducing targeted behavior (e.g., aggression) and improving task completion. For all participants, more than one prompting strategy was effective when positive was combined with negative reinforcement in the DRA. We then implemented a concurrent-chains assessment to determine client preference, a rank-order task for caregiver preference, and an acceptability questionnaire for therapists. Two participants demonstrated a clear preference, and preference was obtained from a total of two caregivers and seven therapists. The initial and repeated verbal prompts were most preferred. Results are discussed in the context of client autonomy and incorporating choice in treatment planning.